Self Disclosure Analysis of Alter Account Users on Twitter: A Social Media Study - Aristyawati, Anak Agung Istri Via; Wulanyani, Ni Made Swasti; Devapramod (Sinergi International Journal of Psychology, 2023)
Social media is something that cannot be separated from the life of a society that is very attached to technology. With social media, people can easily build new identities and express themselves within them. This study aims to analyze Alter account users on Twitter social media to conduct self-disclosure. The method used in this research is descriptive qualitative with social media analysis. The results of the study show that individuals who use alter accounts do self-disclosure because of social influence, new benefits, privacy risks, and a tendency for reciprocity.